Efficacy and safety of subcutaneous rituximab versus intravenous rituximab for first-line treatment of follicular lymphoma (SABRINA): a randomised, open-label, phase 3 trial. Issue 6 (June 2017) - Davies, Andrew; Merli, Francesco; Mihaljević, Biljana; Mercadal, Santiago; Siritanaratkul, Noppadol; Solal-Céligny, Philippe; Boehnke, Axel; Berge, Claude; Genevray, Magali; Zharkov, Artem; Dixon, Mark; Brewster, Michael; et al.
Summary: Background: Intravenous rituximab is the standard of care in B-cell non-Hodgkin lymphoma, and is administered over 1·5–6 h. A subcutaneous formulation could reduce patients' treatment burden and improve resource utilisation in health care. We aimed to show the pharmacokinetic non-inferiority of subcutaneous rituximab to intravenous rituximab in follicular lymphoma and to provide efficacy and safety data. Methods: SABRINA is a two-stage, randomised, open-label phase 3 study at 113 centres in 30 countries. Eligible patients were aged 18 years or older and had histologically confirmed, previously untreated, CD20-positive grade 1, 2, or 3a follicular lymphoma; Eastern Co-operative Oncology Group performance statuses of 0–2; bidimensionally measurable disease (by CT or MRI); life expectancy of 6 months or more; adequate haematological function for 28 days or more; and one or more symptoms requiring treatment according to the Groupe d'Etudes des Lymphomes Folliculaires criteria. Patients were randomly assigned (1:1) by investigators or members of the research team via a dynamic randomisation algorithm to 375 mg/m 2 intravenous rituximab or 1400 mg subcutaneous rituximab, plus chemotherapy (six-to-eight cycles of cyclophosphamide, doxorubicin, vincristine, and prednisone [CHOP] or eight cycles of cyclophosphamide, vincristine, and prednisone [CVP]), every 3 weeks during induction, then rituximab maintenance every 8 weeks. Randomisation was stratified by selected chemotherapy, Follicular Lymphoma International Prognostic Index, and region. The primary endpoint for stage 2 was overall response (ie, confirmed complete response, unconfirmed complete response, and partial response) at the end of induction. Efficacy analyses were done in the intention-to-treat population. Pooled data from stages 1 and 2 are reported on the basis of the clinical cutoff date of the last patient completing the maintenance phase of the study. This trial is registered withClinicalTrials.gov, numberNCT01200758 ; new patients are no longer being recruited, but some patients are still being followed up. Findings: Between Feb 15, 2011, and May 15, 2013, 410 patients were randomly assigned, 205 to intravenous rituximab and 205 to subcutaneous rituximab. Investigator-assessed overall response at the end of induction was 84·9% (95% CI 79·2–89·5) in the intravenous group and 84·4% (78·7–89·1) in the subcutaneous group. The frequency of adverse events was similar in both groups (199 [95%] of 210 in the intravenous group vs 189 [96%] of 197 in the subcutaneous group); the frequency of adverse events of grade 3 or higher was also similar (116 [55%] vs 111 [56%]). The most common grade 3 or higher adverse event was neutropenia, which occurred in 44 patients (21%) in the intravenous group and 52 (26%) in the subcutaneous group. Serious adverse events occurred in 72 patients (34%) in the intravenous group and 73 (37%) in the subcutaneous group. Administration-related reactions occurred in 73 patients (35%) in the intravenous group and 95 (48%) patients in the subcutaneous group (mainly grade 1 or 2 local injection-site reactions). Interpretation: Intravenous and subcutaneous rituximab had similar efficacy and safety profiles, and no new safety concerns were noted. Subcutaneous administration does not compromise the anti-lymphoma activity of rituximab when given with chemotherapy. Funding: F Hoffmann-La Roche.